1986
DOI: 10.1080/08838158609386627
|View full text |Cite
|
Sign up to set email alerts
|

Uses of political computer bulletin boards

Abstract: Research was conducted to investigate electorate motivations for using political computer bulletin board systems (BBSs) and the satisfactions obtained from use. Results from a telephone survey of 117 political BBS users indicated that surveillance and curiosity were the most commonly mentioned motivations for political BBS use. Overall political BBS use was motivated equally by surveillance, personal identity, and diversion motives. The BBS was evaluated most highly for satisfying surveillance needs.Political … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(61 citation statements)
references
References 10 publications
0
59
0
2
Order By: Relevance
“…The text-based design of the Wiki system stated above supports what Garramone, Harris and Anderson (1986) proposed, namely that the lower the level of social presence, the lower the interaction created. Individual relations, dynamic relations, and group relations are three operatives of social influence.…”
Section: Factors Affecting the Intention Of Using Wiki For Collaboratmentioning
confidence: 58%
“…The text-based design of the Wiki system stated above supports what Garramone, Harris and Anderson (1986) proposed, namely that the lower the level of social presence, the lower the interaction created. Individual relations, dynamic relations, and group relations are three operatives of social influence.…”
Section: Factors Affecting the Intention Of Using Wiki For Collaboratmentioning
confidence: 58%
“…En la comunicación en línea, el lenguaje usado y las aplicaciones que se le da, es esencial para un aprendizaje colaborativo. Diversos estudios (Garramone, Harris & Anderson, 1986;Perse, Burton, Kovner, Lears, & Sen, 1992), han manifestado que existe una relación positiva entre la presencia social y la percepción de los estudiantes sobre su experiencia informática. · Interactividad: incluye la comunicación activa y los estilos de comunicación que se utilizan, tales como tiempo de respuesta, los estilos de comunicación, los tipos de tareas, los temas y el tamaño de los grupos.…”
Section: El Concepto De Presencia Socialunclassified
“…However, recent studies have shown social presence is a significant factor to improve instructional effectiveness. Garramore, Harris, and Anderson (1986) concluded the degree of social presence on computer bulletin boards was perceived as higher for users who were more interactive than for those who were not. Richardson and Swan (2003) found students with high overall perceptions of social presence scored high in terms of perceived learning and perceived satisfaction with the instructor.…”
Section: Social Presencementioning
confidence: 99%
“…Social presence has been associated with enhanced online social interactions (Tu & McIssac, 2002). Moreover, when the level of social presence is low, interaction is also low (Garramone, Harris, & Anderson, 1986).…”
Section: Social Interactionmentioning
confidence: 99%
See 1 more Smart Citation